KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN BUDAYA LITERASI DI SEKOLAH DASAR TANJUNG REDEB - Lailan Sawiyah Siagian; Widyatmike Gede Mulawarman; Akhmad Akhmad; Laili Komariyah; Azainil Azainil; Nurlaili Nurlaili (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2020)
Literacy culture is a crucial factor in improving the quality of primary education. The school principal plays a strategic role in managing and developing literacy programs to ensure their effectiveness and sustainability. This study aims to analyze the principal's leadership management in enhancing literacy culture in public elementary schools. The approach used is qualitative with a phenomenological method to explore the experiences of school principals in fostering literacy culture. Data were collected through in-depth interviews, observations, and document analysis. The data analysis technique employed the interactive model of Miles and Huberman, which includes data reduction, data presentation, and conclusion drawing. The findings indicate that SD Negeri 019 focuses on optimizing the library. The principal implements transformational and participatory leadership in building a literacy culture. The main challenges include low student reading interest and a lack of parental support. To address these issues, the principal enhances teacher involvement, collaborates with literacy communities, and utilizes digital technology in literacy programs. This study confirms that adaptive and innovative school leadership can significantly improve literacy culture.